2013
DOI: 10.1093/jat/bkt053
|View full text |Cite
|
Sign up to set email alerts
|

Four Fatalities Involving 5-IT

Abstract: The new designer drug 5-(2-aminopropyl)indole (5-IT) is an indole derivative with stimulant properties. Its synthesis was first described by Albert Hofmann and Franz Troxler in 1962. We report four deaths associated with 5-IT and a validated high-performance liquid chromatography method for quantitation of the drug. In all four deaths, an autopsy was performed, and femoral venous blood, heart blood, urine and vitreous humor were submitted for toxicological analysis. The blood specimens were subjected to compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…The observed symptoms were also severe and similar to those observed with AMT and the plasma levels ranged from 0.015 to 0.59 mg/L [9]. Four fatalities involving 5-IT were also described with femoral blood levels ranging from 0.4 to 1.0 mg/L [10].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The observed symptoms were also severe and similar to those observed with AMT and the plasma levels ranged from 0.015 to 0.59 mg/L [9]. Four fatalities involving 5-IT were also described with femoral blood levels ranging from 0.4 to 1.0 mg/L [10].…”
Section: Discussionsupporting
confidence: 67%
“…AMT was also described as a recreational substance for its intense hallucinogenic properties, first by Alexander Shulgin and more recently in some clinical cases of exposure and even in fatal intoxications [6][7][8]. 5-(2-aminopropyl)-indole (5-IT), described for its similar properties [9,10], and N-methyltryptamine (NMT) are two AMT isomeric substances (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Forensic and pathological investigation of these deaths revealed that a majority involved the presence of 5-IT in combination with other drugs of abuse or prescribed medications, whereas only two cases involved 5-IT alone. Reports of non-fatal intoxications with 5-IT are consistent with a sympathomimetic toxidrome similar to the effects of prototypic stimulant drugs (Bäckberg et al, 2014; EMCDDA, 2014; Seetohul and Pounder 2013). 5-IT, originally synthesized as a stimulant in the 1960s (Hofmann and Troxler 1963; Troxler et al 1968), now joins the list of psychoactive substances being diverted and sold for recreational purposes, and may to be one of the newest MDMA replacements (EMCDDA, 2013a, 2014; Seetohul and Pounder, 2013).…”
Section: 0 Introductionmentioning
confidence: 81%
“…Specifically, a cluster of fifteen fatalities associated with the misuse of 5-IT was reported in Sweden in 2012 (Seetohul and Pounder, 2013). Forensic and pathological investigation of these deaths revealed that a majority involved the presence of 5-IT in combination with other drugs of abuse or prescribed medications, whereas only two cases involved 5-IT alone.…”
Section: 0 Introductionmentioning
confidence: 99%
“…In the case of mephedrone, there was a notable number of deaths that involved self-harm, mainly from suicidal hanging Cosbey et al, 2013). Other reported and analytically confirmed fatalities involved BZP (Monteiro et al, 2013), cathinones such as methylone, butylone, 2-methylamino-1-(3,4-methylenedioxyphenyl) butan-1-one (bk-MBDB), methcathinone (ephedrone), and 4-methylethcathinone (Rojek, Kłys, Maciów-Głąb, Kula, & Strona, 2014;Zawilska & Wojcieszak, 2013), 5-IT (EMCDDA, 2014c; Kronstrand et al, 2013;Seetohul & Pounder, 2013), 2-DPMP (Corkery, Elliott, et al, 2012), and MDAI (Corkery et al, 2013). The victims usually died due to cardiac arrest and respiratory failure, and less frequently from multiorgan failure, disseminated intravascular coagulation, hemorrhages, and fatal wounds.…”
Section: Deaths Related To the Recreational Use Of Psychostimulant Npsmentioning
confidence: 99%